ANALYSIS OF INCREASING CREDIT ACCOUNTS, DPK AND BANKING FRAUD ON E-KYC PROVIDER BUSINESS GROWTH: OJK REGULATORY SANDBOX AS MODERATION - Achmad Irfan Kamaluddin; Mochammad Chabachib (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Following the issuance of OJK Regulation (POJK) Number 13 of 2018 concerning Digital Financial Innovation in the Financial Services Sector, Digital Financial Innovation (IKD) has continued to increase since 2018. To strengthen IKD, OJK issued SEOJK No. 21/SEOJK.02/2019 concerning Implementation of the Regulatory Sandbox for Digital Financial Innovation Organizers.This research aims to analyze the influence of the development of the banking industry, which is proxied through an increase in the number of credit accounts and third party funds (DPK), as well as an increase in fraud cases, on the business growth of E -KYC (electronic-know-your-customer) providers in the 2019-2023. Through a causality approach and multiple linear regression analysis, this study produces empirical findings about the factors that influence E-KYC business growth. Furthermore, this research also explores the role of the OJK regulatory sandbox as a moderating variable in this relationship.The research results found that the growth of credit accounts, the growth of Third Party Fund (DPK) accounts had a positive effect on the business growth of E-KYC providers and the regulatory sandbox as a moderating variable strengthened the positive effect.Keywords: Electronic Know Your Customer, Credit Accounts, Third-Party Funds, Banking Fraud, Regulatory Sandbox